KAMPANYE SOSIAL MENGATASI BAHAYA SEDENTARY LIFESTYLE PADA REMAJA - Muhamad Samsu Ali Aji; Husni Mubarat; Heri Iswandi (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : Sedentary lifestyle or a lifestyle that lacks physical activity refers to the habit of individuals who tend to spend time in a sitting or lying position with little or no physical activity. This can be caused by various factors, including jobs that require a lot of time in front of a computer, attention-grabbing digital entertainment, and reliance on automated tools to carry out daily tasks. If a sedentary lifestyle continues, it can increase the risk of developing chronic diseases, such as: Obesity, Cardiovascular Disease, Hypertension, Stroke, Type 2 Diabetes Mellitus, Osteoporosis, anxiety and other mental health disorders, and even the risk of premature death. The problem solving process in this campaign uses the design thought method which consists of five stages, namely empathize, define, ideate, prototype and test. Data collection was carried out in several stages, including observation, interviews and documentation. The data was then processed and analyzed so that a solution was found, namely a social campaign to increase awareness among teenagers about the importance of physical activity and the dangers of a sedentary lifestyle. Through a program called GERAFIK (Physical Activity Movement) which aims to increase awareness about the importance of physical activity among teenagers in the city of Palembang.